The Effectiveness of Earthquake Preparation Program by Nurses in Elementary School in Chiangrai’s Risk Area: Pilot Study - Sookkoe, Panjapa; Roykulcharoen, Varunyupa; Sriyarat, Kruewan; Rojanaprasert, Pilailak; Kosuwan, Suwith; Petcharaburanin, Krichpet (Journal of The Royal Thai Army Nurses, 2020)
This research was a one group pretest-posttest quasi-experimental design. The purposes of the study here to examine the effectiveness of the “Earthquake Preparation Program” for students, teacher and staff in elementary schools in high risk areas in Chiang Rai on knowledge about earthquakes and survival in earthquake situations, self-efficacy perception and behavior in coping with simulated earthquake situation. Randomly selected by 1 school consisting of 36 students, teacher and staff. The sample received the preparation program for the earthquake situation of 2 ½ days. Data more collected by using the earthquake knowledge and survival questionnaire, self-efficacy in perception for earthquake questionnaire and the behavior observation form to simulated earthquake simulations. Data was collected immediately after receiving the program and repeated measurements in the 3rd and 6th months after the program participation. Repeated measure ANOVA was used to analyze the data. The results showed that students, teachers and staff group; there were statistically significant higher mean scores of knowledge, self-efficacy perception, and behavior in coping earthquake simulated situation immediately right after receiving the program, while after 3 months and after 6 months than prior participating in the program at p value < .01. The results of the research can be used as a guideline for nurses in disaster management to prepare for the earthquake preparedness training for schools. In addition for the results of the research can improve nursing competency to have skills in school disaster management effectively.